The Impact of Auditory Intellectually Repetition (AIR) Learning Model on Elementary School Students’ Mathematical Problem-Solving Abilities - Fatkhul Arifin; One Sukowati; Rohmat Widiyanto (Jurusan PGMI FTIK IAIN Metro Lampung, 2020)
The research method used is quasi-experimental with one group pretest-posttest research design. The withdrawal of the sample size in this study consisted of 29 experimental class students and 28 control class students. Indicators of problem-solving abilities were understanding the problem, planning the problem solving, solving the problem, and interpreting the solution obtained by concluding the outcome of the problem-solving. Based on the results of the posttest, the mathematical problem-solving ability of students taught with the AIR Model is higher than those not taught using the AIR model. This can be seen from the average posttest score of students' mathematical problem-solving abilities taught by the AIR model is 80.62 and the average value of the posttest's mathematical problem-solving abilities of students who are not taught with the AIR model is 73.00. From the t-test results, 0.005 was obtained at a significance level of 0.05 (0.005 ≤ 0.05). It can be concluded that the use of the Auidotory Intellectually Repetition (AIR) model influences the mathematical problem-solving ability of elementary school students.